Association of periodontal health with physical and emotional well-being among pre and postmenopausal women in Bangalore: a cross sectional study - L., Angelin Mary; Shanbhag, Namita; Puranik, Manjunath P. (International Journal of Research in Medical Sciences, 2023)
Background: Menopausal transition is frequently accompanied by physical, emotional as well as periodontal health changes in pre and postmenopausal women due to the decline in circulating blood oestrogen levels. Aim was to investigate the association of periodontal health with physical and emotional well-being among pre and postmenopausal women aged 35-65 years. Methods: A cross sectional study was conducted among 150 pre and 150 postmenopausal women in Bangalore urban district Women Health Questionnaire was used to assess physical and emotional well-being. WHO Oral Health Assessment form for adults 2013 along with plaque and gingival indexes were used to assess the periodontal health status. Descriptive, bivariate, multiple linear regression analysis were carried out. A p<0.05 was considered statistically significant. Results: The mean age among pre and postmenopausal women were 40.09±2.24 years and 55.42±5.7 (p<0.001). The mean scores of depression/anxiety mood; somatic symptoms; memory/concentration; vasomotor symptoms; sleep problem was significantly higher in postmenopausal compared to premenopausal group (p<0.001). The mean number of teeth with gingival bleeding (12.93±8.0 and 6.94±5.68); deep periodontal pocket (2.05±1.61 and 0.44±0.97) were higher in postmenopausal group in comparison to the other group respectively (p<0.001). Depression was significantly associated with periodontal health of women in both the groups. Conclusions: Women after menopause experienced more physical and emotional changes. Periodontal health status was found to be poor among postmenopausal women compared to premenopausal women.